Instability of the Nematic-like Phases Filled with Impurities Against the Formation of Modulated Structures - Kleshchonok, A.V.; Reshetnyak, V.Yu.; Tatarenko, V.A. (Український фізичний журнал, 2010)
We examine spatial distribution of impurity rigid-sphere-like macroparticles in the mesomorphic liquid crystal host. Using continuum statistical mechanical theories, we analyze the thermodynamic conditions necessary for a modulated lamellar-structure to appear. There is a long-range effective interaction between the impurity particles. This interaction is considered as being responsible for the formation of superstructures. In the general case, this interaction includes two components: a van der Waals-type direct interaction and an indirect interaction (through the director-field distortions). The last one depends on both the temperature of a sample and the concentration of particles. This effective interaction controls the structure and properties of the system. Analytical solutions for a director-field distortion, density inhomogeneity of the host medium, temperature of the formation of a modulated structure, and its spatial period are obtained. The proposed theoretical approach can be applied to other anisotropic and inhomogeneous systems. Розглянуто просторовий розподiл домiшкових жорстких сфероподiбних макрочастинок у мезоморфному рiдкокристалiчному носiї. Використовуючи континуальнi статично-механiчнi теорiї, проаналiзовано термодинамiчнi умови, необхiднi для появи модульованих шаруватих надструктур. Мiж домiшковими частинками присутня ефективна далекодiйна взаємодiя. Вважається, що вона вiдповiдає за формування структур. У загальному випадку така взаємодiя мiстить два внески: пряму взаємодiю типу Ван-дер-Ваальса та непряму (через поле викривлення директора). Остання залежить вiд температури зразка та концентрацiї частинок. Ця ефективна взаємодiя контролює структуру та властивостi системи. Було одержано аналiтичнi розв’язки для розподiлу поля директора, неоднорiдностi густини носiя, температури формування модульованих структур та їх просторового перiоду. Запропонований теоретичний пiдхiд може бути застосований до iнших анiзотропних та неоднорiдних систем.